2016
DOI: 10.1089/cbr.2016.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of a Physiologically Based Pharmacokinetic Model Used for Treatment Planning in Peptide Receptor Radionuclide Therapy

Abstract: The aim of this work was to evaluate the sensitivity of time-integrated activity coefficients (TIACs) on the erroneously chosen prior knowledge in a physiologically based pharmacokinetic (PBPK) model used for treatment planning in peptide receptor radionuclide therapy (PRRT). Parameters of the PBPK model were fitted to the biokinetic data of 15 patients after the injection of (111)In-DTPAOC. The fittings were performed using fixed parameter values taken from literature as prior knowledge (reference case, Ref).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The latter were obtained from the fit of the PBPK model to individual biokinetic data. Our previous study showed a marginal effect of changed fixed parameters to the estimation of individual TIACs 25 . Therefore, in this study, we investigated the effect of the interindividual variability of the estimated parameters (Table I) on the variability of the ADs in 177 Lu‐labeled PSMA‐targeting radioligand therapy using a GSA and a PBPK model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter were obtained from the fit of the PBPK model to individual biokinetic data. Our previous study showed a marginal effect of changed fixed parameters to the estimation of individual TIACs 25 . Therefore, in this study, we investigated the effect of the interindividual variability of the estimated parameters (Table I) on the variability of the ADs in 177 Lu‐labeled PSMA‐targeting radioligand therapy using a GSA and a PBPK model.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,24 The PBPK model for the 177 Lu-labeled PSMA-targeting radioligand therapy contains many fixed parameters that have been shown to have a marginal effect to the estimation of individual TIACs. 25 Therefore, the input of interest, as the subject of the GSA analysis, are those parameters which have been estimated from the biokinetic data of the patient population. 18 The list of the investigated parameters in this study is shown in Table I.…”
Section: A Biokinetic Data Pbpk Model Parameters Interindividuamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that the determination of TIACs is little affected by some erroneously chosen fixed parameters for this PBPK model. 50 Nevertheless, the quality of some fixed parameters which are taken from previous studies should be improved to increase the accuracy of the TIAC determination. For example, using measured dissociation rates k off for each substance instead using k off derived from DOTA-RGD for all substances.…”
Section: Discussionmentioning
confidence: 99%
“…PBPK models have been proven to be a powerful method to analyse, simulate and predict the biodistribution of radiolabelled substances (10)(11)(12)(13)(14)(15)(16)(17)(18). The effect of different biodistributions during pre-therapeutic and therapeutic stage can be included in the PBPK model.…”
Section: Zusammenfassungmentioning
confidence: 99%